KONFLIK SOSIAL DALAM CERPEN “TEPI SHIRE” KARYA TAWAKAL M. IQBAL: ANALISIS SOSIOLOGI SASTRA - Balkis Nur Azizah; Abdul Muntaqim Al Anshory (STKIP Siliwangi, 2022)
This study aims to: (1) describe the form of social conflict; (2) reveal the causes of social conflict; and (3) understand the negative and positive impacts of the social conflict. This study uses qualitative, descriptive, and literature. The primary data source is the short story “Tepi Shire”, while the secondary data source is articles and books on the sociology of literature. Data collection techniques using reading and note-taking techniques. The researcher's data analysis techniques include data reduction, data presentation, and conclusion drawing. The results in this study are (1) the implementation of social conflicts in the form of an introvert, indifference, self-defense, and nepotism; (2) the cause of the social conflict is the difference in opinion and interests; (3) negative impacts, namely: causing loss of social interaction, harming oneself and others, being labeled ugly in the eyes of others. The positive impact is that it can increase concentration, strengthen yourself from insults, is not easily disturbed by others, and there is an urge to improve yourself. This research is expected to complement the results of previous research on social conflict in literary works and become a reference material for other researchers who want to study the sociology of literature.